THE ROLE OF STARTUPS IN THE GENERATION OF INNOVATIVE YOUNG ENTREPRENEURS - S. Smadi – Delcheva (Trakia Journal of Sciences)
Aims. The modern entrepreneurial ecosystem builds startups as companies that play a significant role in the business environment. Building the image of innovative entrepreneurs, who are increasingly perceived as paradigm changers, because of the way of thinking that through its creativity and enthusiasm changes the overall entrepreneurial environment. Materials and methods. Presentation of a brief overview of the literature review on the topic of startup companies and their modern vision. Results. A brief overview of current information about startup companies and their specifics. Conclusion. The development of innovation in doing business is not only due to increasing competition in local and global markets, but also as a result of the identification of trends. The concept of a startup includes a business vision in the field of innovation and high technology. Rapid growth is a key feature and unifying factor - the whole process from start-up through growth to startup development is extremely dynamic and limited in terms of time and compared to the pace at which small and medium-sized businesses are developing.